Connector Based Metamodel For Architecture Description Language - Amirat, Abdelkrim; Oussalah, Mourad (INFOCOMP Journal of Computer Science, 2009)
To provide hierarchical description from different software architectural viewpoints we need more than one abstraction hierarchy and connection mechanisms to support the interactions among components. Also, these mechanisms will support the refinement and traceability of architectural elements through the different levels of each hierarchy. Current methods and tools provide poor support for the challenge posed by developing system using hierarchical description. This paper describes an architecture-centric approach allowing the user to describe the logical architecture view where a physical architecture view is generated automatically for all application instances of the logical architecture.